CRISPR Ribonucleoprotein-Mediated Precise Editing of Multiple Genes in Porcine Fibroblasts - Xiaochen Guo; Chang Liu; Yunjing Zhao; Chaoqian Jiang; Junxue Jin; Zhonghua Liu; Yanshuang Mu (Animals, 2024)
The multi-gene editing porcine cell model can analyze the genetic mechanisms of multiple genes, which is beneficial for accelerating genetic breeding. However, there has been a lack of an effective strategy to simultaneously perform precise multi-gene editing in porcine cells. In this study, we aimed to improve the efficiency of CRISPR RNP-mediated precise gene editing in porcine cells. CRISPR RNP, including Cas9 protein, sgRNA, and ssODN, was used to generate precise nucleotide substitutions by homology-directed repair (HDR) in porcine fetal fibroblasts (PFFs). These components were introduced into PFFs via electroporation, followed by PCR for each target site. To enhance HDR efficacy, small-molecule M3814 and phosphorothioate-modified ssODN were employed. All target DNA samples were sequenced and analyzed, and the efficiencies of different combinations of the CRISPR RNP system in target sites were compared. The results showed that when 2 μM M3814, a small molecule which inhibits NHEJ-mediated repair by blocking DNA-PKs activity, was used, there was no toxicity to PFFs. The CRISPR RNP-mediated HDR efficiency increased 3.62-fold. The combination of CRISPR RNP with 2 μM M3814 and PS-ssODNs achieved an HDR-mediated precision gene modification efficiency of approximately 42.81% in mutated cells, a 6.38-fold increase compared to the control group. Then, we used the optimized CRISPR RNP system to perform simultaneous editing of two and three loci at the INS and RLN3 genes. The results showed that the CRISPR RNP system could simultaneously edit two and three loci. The efficiency of simultaneous editing of two loci was not significantly different from that of single-gene editing compared to the efficiency of single-locus editing. The efficiency of simultaneous precise editing of INS, RLN3 exon 1, and RLN3 exon 2 was 0.29%, 0.24%, and 1.05%, respectively. This study demonstrated that a 2 μM M3814 combination with PS-ssODNs improves the efficacy of CRISPR RNP-mediated precise gene editing and allows for precise editing of up to three genes simultaneously in porcine cells.